Research on correlation between compression index (Cc) with other properties of soil for geotechnical design in Sihanoukville city; Проблемы геологии и освоения недр; Т. 1 - Hoang Anh Tuan; Doan Cong Bien; Nguyen Ba Dong; Nguyen Hai Ha; Phi Hong Thinh (Гидрогеология и инженерная геология. Геоинформационные системы в гидрогеологических исследованиях, 2017)
Заглавие с экрана